20,000 Leagues Under the Sea Based on a Novel by Jules Verne - Perez Rosso, Orlando (The Masters of Cinema Series, 2021)
The French scientist Arronax joins the US Navy on the search for a sea monster, which is terrorizing shipping. But their US ship, "The Abraham Lincoln", has its rudder rammed by the monster, which turns out to be a submarine. The submarine’s creator Captain Nemo reluctantly rescues Arronax and his party after they are thrown overboard. Aboard the submarine, they witness the marvels of Nemo’s invention and the wonders of the seabed. At the same time a group of soldiers escape a Confederate prison by balloon and land on a nearby island. Nemo secretly aids them with supplies. One of the castaways, Harding, befriends a savage girl living on the island, but she is soon fought over by the other soldiers. At the same time Charles Denver, a man from Nemo’s past, arrives on the island ... "Twenty Thousand Leagues Under the Sea" is an absolutely fascinating artifact from the silent era. Although prints have been in circulation for many years, it was not until its video release in the 1990s that many people had the opportunity to see this previously obscure film. It is a fascinating relic that shows just how accomplished early filmmaking was. [www.moria.co.nz]